Translating idioms : A study on Remedy Entertainment’s Ahti and his idioms - Öström, Sami (My University, 2025)
Video game translation has been a relatively new subject amongst academics due to video games’ relatively short existence of approximately 50 years. In this thesis I expand this field by focusing on a specific character with a very specific niche: Remedy Entertainment’s Ahti and the idioms he uses in his dialogue. These idioms sound nonsensical since they are directly translated from Finnish idioms. My research question concerned the purpose of this kind of translational creative choice for the character. To conduct the research for my thesis, I analyzed Evelyn Nien-Ming Ch'ien’s (2008) concept of weird English and Hans Vermeer’s (1978) Skopos theory to find out both the purpose of this kind of translational creative choice and how it actively appears in Ahti’s dialogue throughout his appearances. To understand the character and his idioms better, one needs to understand the importance of cultural knowledge and more specifically, the Finnish culture and the common use of idioms in this language. Direct translation is not always the best choice since many cultural nuances can and will be lost this way. However, in Ahti’s case his directly translated idioms are meant to be confusing while simultaneously being humorous and mystifying for the sake of making the character more enigmatic. For this exact reason, my research concluded that direct translation for his idioms was the best choice.
Keywords: video game translation, localization, video games, cultural knowledge, idioms, weird English, Skopos theory